The Use of Modeling Strategy in Improving Students’ Descriptive Texts Comprehension - Evi Suzanna Evi Suzanna; Nuzulul Isna (Universitas Islam Negeri Palopo, 2025)
The aim of this research is to examine how well the modeling method improves EFL students' understanding of descriptive texts. A total of fifty-nine seventh-grade students from SMPN 2 Susoh were split into experimental and control groups for this quasi-experimental study. Traditional training was given to the control group, whereas the experimental group was taught a modeling method that included four stages: text modeling, deconstruction, co-construction, and self-construction. SPSS version 26, which featured independent samples t-tests, normality, homogeneity, and descriptive statistics, was utilized to assess the data. The experimental group improved by an average of 40.62 points on the post-test, whereas the control group improved by 39.71 points, according to the results. Statistical significance was achieved by the change (p =.042). As a result, the modeling technique has a somewhat positive effect on students' comprehension and composition of descriptive texts. These findings imply that the modeling strategy provides a methodical and successful teaching approach for junior high school English instruction, especially in the setting of EFL.